Telephone Workers' Reaction to the New Technology - Zureik, Elia; Mosco, Vincent; Lochhead, Clarence (Relations industrielles / Industrial Relations, 1989)
The purpose of this study is to provide data that shed light on the reactions of workers to the introduction ofthe new technology in three différent occupational groups within a segment of the Canadian téléphone industry